2018
DOI: 10.1017/s0014479718000224
|View full text |Cite
|
Sign up to set email alerts
|

Transgressive Segregation, Heterosis and Heritability for Yield-Related Traits in a Segregating Population of Pisum Sativum L.

Abstract: SUMMARYPea is a self-pollinated, diploid (2n = 14), annual crop produced worldwide for human consumption and animal feed. The exploitation of maximum genetic potential from available pea resources implies the knowledge of genetic parameters of yield components. Hence, the present study was conducted in a cross between two pea varieties, namely DDR14 and Explorer, its F2 progeny and F3 families to find out transgressive segregants and to determine the magnitude of narrow sense heritability and heterosis. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…The interaction of many traits establishes the yield, and hence yield is called a quantitative trait (Guindon et al, 2018). While optimum vegetative growth during crop establishment is required to achieve the maximum yield potential, the desirable plant type in garden pea is the one that has dwarf growth habit and does not need support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of many traits establishes the yield, and hence yield is called a quantitative trait (Guindon et al, 2018). While optimum vegetative growth during crop establishment is required to achieve the maximum yield potential, the desirable plant type in garden pea is the one that has dwarf growth habit and does not need support.…”
Section: Discussionmentioning
confidence: 99%
“…Heterosis has been predicted in pea long back; however, cleistogamous nature of flower and non-availability of genetic mechanisms like male sterility limit the exploitation of heterosis. Even so, potential crosses likely to produce transgressive segregants could be achieved simply through the selection of superior individual progenies from a range of existing possibilities (Guindon et al, 2018). The success of breeding programme depends on the initial population used or the parents involved to create such populations.…”
Section: Introductionmentioning
confidence: 99%
“…Both phenomena are predicted to produce more exaggerated hybrid phenotypes with increasingly divergent parental lineages (Guindon, Martin, Cravero, & Cointry, 2019). Furthermore, heterosis has been used in many studies to predict the successful establishment of transgressive phenotypes in subsequent generations (Chahota, Kishore, Dhiman, Sharma, & Sharma, 2007;Guindon et al, 2019;Khan, Mahbub, Reza, Shirazy, & Mahmud, 2016;Kumar, Jeberson, Singh, & Sharma, 2017). These studies of agricultural crops highlight the importance of examining trait values in the F1 hybrid stage to make meaningful predictions about long-term success.…”
Section: Transgressive Hybrid Phenotypesmentioning
confidence: 99%
“…As recent evidence continues to highlight the importance of epistasis and epigenetics in driving transgressive phenotypes at the F1 stage (Jiang et al, 2017), it is likely that these mechanisms contribute to fixed transgressive phenotypes in admixed populations. Furthermore, in many agricultural studies, the extent of observed heterosis helps predict the successful establishment of transgressive phenotypes in subsequent generations (Chahota et al, 2007; Guindon et al, 2019; Khan et al, 2016; Kumar et al, 2017; Sarawat et al, 1993). In the case of wild non‐native hybrids, it is similarly useful to analyse phenotypic traits in F1 hybrids to understand the potential advantages and adaptations that may arise through transgressive segregation.…”
Section: Introductionmentioning
confidence: 99%
“…Though often considered separately, heterosis and transgressive segregation are linked processes that can produce transgressive hybrid phenotypes. Both are predicted to produce more exaggerated phenotypes with increasingly divergent parental lineages (Guindon et al, 2019; Stelkens & Seehausen, 2009). As recent evidence continues to highlight the importance of epistasis and epigenetics in driving transgressive phenotypes at the F1 stage (Jiang et al, 2017), it is likely that these mechanisms contribute to fixed transgressive phenotypes in admixed populations.…”
Section: Introductionmentioning
confidence: 99%